2012
DOI: 10.1007/s00405-012-2200-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of branchial cleft anomalies in UKMMC: a 10-year retrospective study

Abstract: Branchial cleft anomalies result from abnormal persistence of branchial apparatus, which is located at the lateral part of the neck. These occur due to failure of obliteration of the branchial apparatus during embryonic development. Differential diagnoses of lateral neck mass are salivary gland or neurogenic neoplasms, paragangliomas, adenopathies, cystic hygroma or cystic metastasis from squamous cell carcinoma or thyroid papillary carcinoma. Clinically, a branchial cyst is smooth, round, fluctuant and non-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 14 publications
1
70
0
Order By: Relevance
“…Thyroid scintigraphy (with technetium-99) is very useful in diagnosis, especially in case of ectopic thyroid tissue. FNA cytology examination, plus thorough endoscopy of the upper respiratory system should be performed, for exclusion of metastatic or inflammatory adenopathy [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thyroid scintigraphy (with technetium-99) is very useful in diagnosis, especially in case of ectopic thyroid tissue. FNA cytology examination, plus thorough endoscopy of the upper respiratory system should be performed, for exclusion of metastatic or inflammatory adenopathy [3].…”
Section: Discussionmentioning
confidence: 99%
“…Branchial cysts are the result of branchial apparatus obliteration failure during the first stage of embryonic life and originate from the second (95%), the first (8% -10%), the third (2% -8%) and the fourth (1% -2%) branchial remnant [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-operative complications include cranial nerves injury(3.5%), damage to internal jugular vein, formation of persistent fistula, local infection, seroma, hematoma or scar formation(3.3%) (11,19). The overall recurrence rates following surgery were 3-4.9% in retrospective studies of 98 and 183 patients (3,11).However, the recurrence rate may be as high as 22% if there is a history of infections or incomplete operation (20).…”
Section: Discussionmentioning
confidence: 99%
“…Branchial cysts have no external or visceral opening and thus retain secretions, while branchial sinuses are blind ending tract communicating with the skin or the pharyngeal lumen; finally, fistulas are tracts connecting the pharynx to the skin [8,10]. Branchial cyst was first described by Ascherson in 1832, who suggested that this resulted from the impaired obliteration of the branchial cleft or pouches; these are the most common congenital masses of the lateral neck and they represent 20-80 % of the branchial anomalies [11,12].…”
Section: Introductionmentioning
confidence: 98%